2004
DOI: 10.1111/j.1469-8137.2004.01107.x
|View full text |Cite
|
Sign up to set email alerts
|

The antifungal Dm‐AMP1 protein from Dahlia merckii expressed in Solanum melongena is released in root exudates and differentially affects pathogenic fungi and mycorrhizal symbiosis

Abstract: Summary• Transformed aubergine plants constitutively expressing the Dm-AMP1 antimicrobial defensin (from Dahlia merckii ) were generated and characterized.• Transgenic plants were selected on kanamycin and screened by polymerase chain reaction analysis. The expression of Dm-AMP1 in plant tissues and its release in root exudates were detected by Western blot analyses. Dm-AMP1 localization was performed by immunohistochemical experiments.• Dm-AMP1 expression ranged from 0.2% to 0.48% of total soluble proteins in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 54 publications
2
27
0
2
Order By: Relevance
“…the lowest levels of infection were observed in t1 and t14 both with size of the lesion 1.19 mm which was 68 % less compared to the control plants. Similar results were obtained in transgenic aubergine plants expressing defensin Dm-AMP1 originated from Dalia (Dahlia merckii) showed resistance to the pathogenic fungus Botrytis cinerea and the leaf infection was reduced by 36 to 100% (30).…”
Section: Molecular Analysis Of Tsupporting
confidence: 78%
“…the lowest levels of infection were observed in t1 and t14 both with size of the lesion 1.19 mm which was 68 % less compared to the control plants. Similar results were obtained in transgenic aubergine plants expressing defensin Dm-AMP1 originated from Dalia (Dahlia merckii) showed resistance to the pathogenic fungus Botrytis cinerea and the leaf infection was reduced by 36 to 100% (30).…”
Section: Molecular Analysis Of Tsupporting
confidence: 78%
“…However, the cellular interactions between host roots and AM fungal hyphae leading to the failure of intraradical colonization in corn lines actively expressing the constitutive insecticidal B. thuringiensis toxin remain to be investigated. Previous works reported that transformed eggplant plants constitutively expressing the Dm-AMP1 antimicrobial defensin from Dahlia merckii releasing the protein in root exudates did not interfere with the host recognition system and symbiosis establishment by the AM fungus G. mosseae (74). Other authors have obtained similar findings, that transgenic Nicotiana sylvestris-and Nicotiana tabacum-expressing chitinases and pathogenesis-related proteins did not influence the establishment of mycorrhizal infection by G. mosseae (76,77).…”
Section: Discussionmentioning
confidence: 70%
“…Crops, fruits, and forest trees exhibit mycorrhizal colonization by arbuscular mycorrhizae, ectomycorrhizae, and ectendomycorrhizae (EEM). While numerous studies have addressed the impact of transgenic plants on arbuscular mycorrhizae (10,26,64,68,72,73) and ectomycorrhizae (32,43,50,60), no previous study focused on EEM.…”
mentioning
confidence: 99%